The grand collaboration: Thomas Jefferson, James Madison, and the invention of American religious freedom - Green, Steven K. (Religious freedom and public dialogue a Robert Nusbaum center series, 2024)
"In this dual biography of Thomas Jefferson and James Madison, constitutional law scholar Steven K. Green demonstrates how their commitment to advancing religious freedom arose chiefly out of larger secular commitments and placed them on the cutting edge of views on church-state separation. In addition, Green explains how their differences regarding freedom of conscience and religious freedom were minimal and not at all contradictory, as others have argued. Nor were their achievements foregone conclusions-indeed, they frequently worked against considerable odds-and they never saw their work as completed"--